PENGARUH DEFERRED TAX EXPENSE DALAM MENDETEKSI EARNINGS MANAGEMENT DENGAN MENGGUNAKAN PENDEKATAN DISCRETIONARY REVENUE - AGNES FEBRIYANTI; HANNA HANNA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
This study examined the effect of deferred tax expense in detecting earnings management by using discretionary revenue model (Stubben 2010). After going through purposive sampling from all of the public companies in Bursa Efek Indonesia during 5 observation years (2008-2012), 113 samples are selected or equal to 565 observation firm years. The result of this research shows that deferred tax expense do not affect earnings management by using discretionary revenue model. This research found that deferred tax expense could not explain earnings management.